ANALISIS PENGARUH PRODUCT, PRICE, PROMOTION, PLACE, PEOPLE, PROCESS, DAN PHYSICAL EVIDENCE TERHADAP KEPUTUSAN PEMBELIAN KATERING DI KAREN KATERING JEMBER - Nauli Elisabeth Rajagukguk, Veranda; Hidayah, Tamriatin; Maspufah, Hayatul (Jurnal Riset Ekonomi, Manajemen, Bisnis dan Akuntansi, 2024)
This study aims to determine the effect of product, price, promotion, place, people, process, and physical evidence on catering purchasing decisions at Karen Katering Jember. This type of research is quantitative with data sources obtained through purposive sampling techniques with questionnaire distribution methods. The data analysis method of this study uses multiple linear regression analysis methods. The results of this study are Product (Significance value of 0.016 <0.050) has a partial effect on purchasing decisions. Price (Significance value of 0.745> 0.050) does not have a partial effect on purchasing decisions. Promotion (Significance value of 0.032 <0.050) has a partial effect on purchasing decisions. Place (Significance value of 0.083> 0.050) does not have a partial effect on purchasing decisions. People (Significance value of 0.867> 0.050) does not have a partial effect on purchasing decisions. Process has a partial effect on purchasing decisions. Physical Evidence (Significance value of 0.000 < 0.050) has a partial effect on purchasing decisions. The conclusion of this study shows that the variables product, promotion, process, and physical evidence have a positive and significant effect on purchasing decisions while the variables place, people and price do not have a significant effect on purchasing decisions.